Struggles for Justice or “Qualified Twaddle”? : A discourse analysis on the media coverage of the mining conflict & activism in Gállok, Sápmi - Litzell, Sara (Linköpings universitet, Tema Miljöförändring, 2018)
A global mining boom has recently occurred and conflicts due to mineral extraction in the context of environmental justice is visible all over the world. A recent conflict in Sweden, is in Gállok where mining exploration has been conducted on the traditional lands of the indigenous Sámi. Activists protested the exploration by occupying the site during three months in 2013. The conflict has received media attention and since media have influence on the public discourse and while Sami rights have received little official recognition in Sweden, this thesis aims at analysing the mining exploitation discourse by scrutinising the media coverage of the activism and conflict in Gállok. Mining advocates emphasise social effects like economic gain, jobs and future prospect and the importance of working co-existence between different stakeholder, while the mining critics stresses the importance of respecting and recognising Sami rights, long-term sustainability and negative social and environmental impacts from mining. The Government and the mining industry are dominant actors within the mining exploration discourse and truth claims of sustainable mining and the green economy, working co-existence and minerals as essential for and a prerequisite for sustainable development supports their interest. The activism and the Sami’s struggles for justice and recognition in Gállok can be regarded as part of the global environmental justice movement. Finally, the Swedish mining policies can be argued to be based on previous colonial politics, contributing to a continued marginalisation and oppression of the Sami people.